Evaluation of Pseudomonas aeruginosa pathogenesis and therapeutics in military‐relevant animal infection models. Issue 7 (15th June 2021) - Bobrov, Alexander G.; Getnet, Derese; Swierczewski, Brett; Jacobs, Anna; Medina‐Rojas, Maria; Tyner, Stuart; Watters, Chase; Antonic, Vlado
Abstract : Modern combat‐related injuries are often associated with acute polytrauma. As a consequence of severe combat‐related injuries, a dysregulated immune response results in serious infectious complications. The gram‐negative bacterium Pseudomonas aeruginosa is an opportunistic pathogen that often causes life‐threatening bloodstream, lung, bone, urinary tract, and wound infections following combat‐related injuries. The rise in the number of multidrug‐resistant P. aeruginosa strains has elevated its importance to civilian clinicians and military medicine. Development of novel therapeutics and treatment options for P. aeruginosa infections is urgently needed. During the process of drug discovery and therapeutic testing, in vivo testing in animal models is a critical step in the bench‐to‐bedside approach, and required for Food and Drug Administration approval. Here, we review current and past literature with a focus on combat injury‐relevant animal models often used to understand infection development, the interplay between P. aeruginosa and the host, and evaluation of novel treatments. Specifically, this review focuses on the following animal infection models: wound, burn, bone, lung, urinary tract, foreign body, and sepsis.